Integrating the clinical pharmacist into the emergency department interdisciplinary team: a study protocol for a multicentre trial applying a non-randomised stepped-wedge study design - Torbjørn Wisløff; Eirik Hugaas Ofstad; Elin C Lehnbom; Renate Elenjord; Renata Vesela; Tine Johnsgård; Birgitte Zahl-Holmstad; Torstein Risør; Lars Røslie; Ole Magnus Filseth; Per-Christian Valle; Kristian Svendsen; et al. (BMJ Open)
Introduction The ‘emergency department (ED) pharmacist’ is an integrated part of the ED interdisciplinary team in many countries, which have shown to improve medication safety and reduce costs related to hospitalisations. In Norway, few EDs are equipped with ED pharmacists, and research describing effects on patients has not been conducted. The aim of this study is to investigate the impact of introducing clinical pharmacists to the interdisciplinary ED team. In this multicentre study, the intervention will be pragmatically implemented in the regular operation of three EDs in Northern Norway; Tromsø, Bodø and Harstad. Clinical pharmacists will work as an integrated part of the ED team, providing pharmaceutical care services such as medication reconciliation, review and/or counselling. The primary endpoint is ‘time in hospital during 30 days after admission to the ED’, combining (1) time in ED, (2) time in hospital (if hospitalised) and (3) time in ED and/or hospital if re-hospitalised during 30 days after admission. Secondary endpoints include time to rehospitalisation, length of stay in ED and hospital and rehospitalisation and mortality rates.Methods and analysis We will apply a non-randomised stepped-wedge study design, where we in a staggered way implement the ED pharmacists in all three EDs after a 3, 6 and 9 months control period, respectively. We will include all patients going through the three EDs during the 12-month study period. Patient data will be collected retrospectively from national data registries, the hospital system and from patient records.Ethics and dissemination The Regional Committee for Medical and Health Research Ethics and Local Patient Protection Officers in all hospitals have approved the study. Patients will be informed about the ongoing study on a general basis with ads on posters and flyers.Trial registration number NCT04722588.